2022
DOI: 10.4103/jfmpc.jfmpc_1984_21
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression among new cancer patients

Abstract: Introduction and Objective: Definitive diagnosis, tedious treatment methods, and long treatment duration are possible factors contributing to psychiatric disorders in cancerous patients, including anxiety and depression. Accordingly, this study aimed to investigate the effective factors on the occurrence of psychiatric disorders in newly diagnosed cancer patients. Methods: This descriptive-analytical study was conducted in Semnan, Iran, in 2018, in which 122 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
2
1
1
Order By: Relevance
“…In our sample, sex was not significantly associated with anxiety, which is in accordance with the findings of Truong et al [ 12 ]. However, this finding differs from that of some other studies that reported a higher prevalence of anxiety in women than in men [ 16 , 35 , 36 ]. Marital status was not significantly associated with anxiety score, and this finding is similar to that of Truong et al [ 12 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our sample, sex was not significantly associated with anxiety, which is in accordance with the findings of Truong et al [ 12 ]. However, this finding differs from that of some other studies that reported a higher prevalence of anxiety in women than in men [ 16 , 35 , 36 ]. Marital status was not significantly associated with anxiety score, and this finding is similar to that of Truong et al [ 12 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study found that 23.9% of the patients presented with anxiety symptoms, 5.4% with mild anxiety, and 18.5% with symptomatic anxiety. Our results were similar to those of Van den Brekel et al and Safaie et al (22% and 28.6%, respectively) [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Incorporating mental therapies into a cancer patient's treatment plan can help control psychiatric illnesses, particularly anxiety and despair, and is recommended as a national health policy by some authors [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…For the time of diagnosis, it was found that patients undergoing treatment for 7-12 months were more satisfied, compared to those with a period of less than 7 months and more than 12 months. Studies on the impact of cancer on patients' mental health and well-being indicate that depression and anxiety can hinder treatment and recovery as well as QoL and survival, and must be diagnosed early so that patients can face each phase of the cancer continuum with the necessary skills (26)(27) .…”
Section: Discussionmentioning
confidence: 99%